Meta Analisis Persepsi Orang Tua Terhadap Penggunaan Gadget Pada Anak Usia Dini - Namirah Thufailah; Dian Nur Zakiyyah; Rika Sri Wahyuni; Fidrayani Fidrayani (Institut Nalanda, 2024)
This research aims to analyze parents' perceptions of gadget use in early childhood. The aim of this research is to determine parents' perceptions of gadget use in early childhood. The method used is meta-analysis, by describing the results of analysis from various studies that have been published nationally in Indonesia, then calculating the effect size. The research sample consisted of ten articles published in accredited national journals in the 2019-2024 period.